2015
DOI: 10.2754/avb201584020153
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the digestive system of ducks depending on sex and genetic background

Abstract: The aim of the study was to determine the effect of genotype and sex on body weight, body dimensions, intestinal length and diameter, percentage of intestinal segments, and weight and percentage of the main internal organs of ducks. The study was performed with 80 Pekin ducks, which were kept throughout rearing (1-49 days of age) in a confinement building and fed commercial waterfowl feed ad libitum. After 7 weeks of rearing, 40 ducks (10 drakes and 10 ducks of hybrid line SM3 Heavy and 10 drakes and 10 ducks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 6 publications
1
10
1
1
Order By: Relevance
“…K2 ducks had significantly shorter body length than KhO1 ducks, and KhO1 ducks significantly shorter intestine than K2 ducks. The intestine length to body length ratios were lower than those reported by Wasilewski et al (2015) for young Pekin ducks. Kokoszyński (2011) observed that four commercial Pekin duck hybrids (Star 53 H.Y., AP54, PP54, and PP45) differed significantly in body weight and length at 7 weeks of age.…”
Section: Resultscontrasting
confidence: 79%
See 3 more Smart Citations
“…K2 ducks had significantly shorter body length than KhO1 ducks, and KhO1 ducks significantly shorter intestine than K2 ducks. The intestine length to body length ratios were lower than those reported by Wasilewski et al (2015) for young Pekin ducks. Kokoszyński (2011) observed that four commercial Pekin duck hybrids (Star 53 H.Y., AP54, PP54, and PP45) differed significantly in body weight and length at 7 weeks of age.…”
Section: Resultscontrasting
confidence: 79%
“…Watkins et al (2004) report, however, that in Pekin ducks, morphological and functional development of the digestive tract is terminated after 7 weeks of age. An earlier study with young Pekin ducks (6-8 weeks of age) found greater (Jamroz et al, 2001;Wasilewski et al, 2015) lengths of individual intestine segments compared to the analysed ducks after two reproductive seasons.…”
Section: Resultsmentioning
confidence: 73%
See 2 more Smart Citations
“…Development rate of digestive tract in birds varies from species to species. Development of digestive tract is related with growth rate of the birds so faster development of digestive tract is characteristic feature of high growing birds (Wasilewski et al, 2015). The development of digestive organs starts just after hatching and the intestine develop rapidly as compare to the other organs of digestive system (Dong et al, 2012).…”
Section: Introductionmentioning
confidence: 99%